Larger Canna Leafroller, Calpodes ethlius (Stoll) (Insecta: Lepidoptera: Hesperiidae) - Heather J. McAuslane; Kim King (EDIS, 2002)
This document is EENY-132, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2000.